2016
DOI: 10.1016/j.jad.2016.02.031
|View full text |Cite
|
Sign up to set email alerts
|

Effect of transcutaneous auricular vagus nerve stimulation on major depressive disorder: A nonrandomized controlled pilot study

Abstract: Background Depression presents a significant burden to both patients and society. One treatment that has emerged is vagus nerve stimulation (VNS), an FDA-approved physical treatment for depressive disorders. However, the application of this intervention has been limited by the involvement of surgery and potential side effects. The aim of this study is to explore the effectiveness of stimulating the superficial branches of the vagus nerve as a solo treatment for MDD. Methods This is a nonrandomized, controlle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
161
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 210 publications
(179 citation statements)
references
References 36 publications
7
161
0
3
Order By: Relevance
“…Lim and colleagues (Lim, Kim, Lee, & Namgung, 2016) found that acupuncture may achieve treatment effects through vagal nerve modulation of inflammatory responses in internal organs. A recent study also showed that direct stimulation of the peripheral branch of the vagus nerve can relieve symptoms in MDD patients (Rong et al, 2016). Taken together, these studies suggest that the vagus nerve may play an important role in acupuncture treatment of depression.…”
Section: Introductionmentioning
confidence: 99%
“…Lim and colleagues (Lim, Kim, Lee, & Namgung, 2016) found that acupuncture may achieve treatment effects through vagal nerve modulation of inflammatory responses in internal organs. A recent study also showed that direct stimulation of the peripheral branch of the vagus nerve can relieve symptoms in MDD patients (Rong et al, 2016). Taken together, these studies suggest that the vagus nerve may play an important role in acupuncture treatment of depression.…”
Section: Introductionmentioning
confidence: 99%
“…A recent tVNS study in migraine patients showed that although both 1 and 25 Hz tVNS can improve clinical outcome in patients with chronic migraine, 1 Hz tVNS can produce greater improvement than 25 Hz tVNS (Straube et al, 2015). Studies have suggested that a frequency between 1 and 30 Hz, pulse width of 130–1000 ÎŒs and intensity of 4–6 mA is sufficient to elicit a therapeutic effect (Fang et al, 2016; Rong et al, 2016). Therefore, the suggested parameters for tVNS treatment of ASD may set a frequency between 1 and 30 Hz, or altered frequency between 1 and 30 Hz.…”
Section: Parameters Of Tvns For Treatment Of Asdmentioning
confidence: 99%
“…Previous studies suggested that stimulation intensity could be set to a level that could arouse a tingling but tolerable sensation (Rong et al, 2016). More research is needed to explore the optimal tVNS parameters for different subgroups of ASD.…”
Section: Parameters Of Tvns For Treatment Of Asdmentioning
confidence: 99%
See 2 more Smart Citations